PERLINDUNGAN TERHADAP PERKEMBANGAN LAYANAN KESEHATAN BERBASIS KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) DI INDONESIA : Protection Regarding the Development of Artificial Intelligence-based Health Service Technology in Indonesia - Primasatya, Sigit (Jurnal Globalisasi Hukum., 2024)
Artificial Intelligence-based (AI) Health Service is a solution to the limited number and distribution of doctors in Indonesia. However, the use of AI technology also presents several challenges. This research used a normative juridical approach to analyse protection regarding the development of AI-based technology-based health services in Indonesia. The analysis shows that challenges to utilizing AI in healthcare include bias, protection of personal data and risk of malpractice. As a system that has no moral values, doctors is expected to be wiser in operating it. To ensure the delivery of quality AI-based health services, patients, doctors, service providers and the government need to understand and carry out their respective roles collaboratively.